The variety of clinical manifestations in the course of granulomatosis with polyangiitis - Metelska, Aleksandra; Metelski, Jakub; Sereda, Dominika; Nieścior, Hubert (Journal of Education, Health and Sport, 2022)
Introduction and purpose Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis, is a rare systemic autoimmune disease. It causes inflammation of small and medium-sized arteries in various organs, with the vessels of the kidneys and lungs being most frequently affected. Characteristic for GPA is the presence of antibodies (ANCA) directed against proteinase-3 (PR3) produced by neutrophils. The aim of the study is to present various clinical manifestations of GPA and current diagnostic tools. Description of the state of knowledge Currently, there is a marked increase in the incidence of GPA. This disease affects both men and women, most often between the ages of 45 and 60. Granulomas typical of GPA consist of giant cells surrounded by plasma cells, lymphocytes and dendritic cells that damage the submucosa and migrate to surrounding tissue, cartilage or bone, causing necrosis and permanent deformation. In making a diagnosis, you can use the ACR criteria and the acronym ELK. Summary GPA is a multi-system disease. Initially, it causes a number of non-specific ailments. The first clinical manifestation is most often otorhinolaryngological symptoms, especially serous otitis media. Then it can gradually cause discomfort from any system. The most frequently involved vessels are the kidneys and lungs, but also the skin, nervous system and eyes. Prompt diagnosis of GPA is very important for prognostic reasons. Early initiation of immunosuppressive therapy can rapidly lead to clinical remission and, in the long term, reduce disease complications and mortality.